The Influence of Globalization on Sustainable Development Policy Formulation and Public Participation in Thailand - Pitilerdsirikul, Napatthika; Wisetchai , Shanasuek (Rajapark Journal, 2026)
This academic article critically analyzes the structural influence of globalization on the formulation of Sustainable Development Goals (SDGs) policies and the subsequent dynamics of public participation within Thai Local Government Organizations (LGOs). The study addresses three core research questions: (1) How does globalization transmit policy norms into Thai local administrative processes? (2) To what extent does this phenomenon affect the patterns of public participation? and (3) How can communities establish horizontal political spaces to autonomously determine their policies? Through a rigorous synthesis of contemporary scholarly literature, the study reveals three main findings. First, globalization transmits norms via compulsory central government indicators, creating a "Structural Paradox" where global decentralization mandates are utilized by the state to re-centralize administrative authority. Second, this top-down enforcement marginalizes public participation into mere "Tokenism," functioning primarily to legitimize pre-determined projects rather than empowering citizens. Third, despite institutional constraints, local communities can establish horizontal spaces through the mechanisms of "Glocalization" and digital platforms. By leveraging robust social capital and civic networks, local actors can negotiate power asymmetries and drive bottom-up policy formulation. Ultimately, the central state must transition from a "Controller" to a "Facilitator" by institutionalizing genuine fiscal and political decentralization, enabling citizens to become active "Co-creators" of sustainable public governance.